Аналіз ефективності антиколізійних механізмів в RFID-мережах - Федота, О. В. (ХНУРЕ, 2020)
In the present work, an analysis of the effectiveness of modern conflict resolution mechanisms in systems created using the Internet of things technologies such as RFID have been proposed. The object of research is the system of accounting and management based on radio frequency identification technology.
Keywords: мережа RFID; ALOHA; RFID